PEMBELAJARAN KRIYA TEKSTIL MENGGUNAKAN KAIN PERCA BATIK DI SMK NEGERI 8 PADANG - Agung Pratama; Ranelis Ranelis (Institut Seni Indonesia Padangpanjang, 2022)
The research entitled “Learning Textile Crafts Using Batik Patchwork at SMK Negeri 8 Padang” is a descriptive study of how the creativity of students and students in developing textile crafts using batik patchwork and the factors causing the low creativity of students and students. This research is a qualitative research where the researcher acts as an instrument that goes directly to the field using data collection methods in the form of observation, interviews, documentation and literature study. The results of this study indicate that the process of making textile crafts using batik patchwork in the form of functional objects is carried out by students and students in various ways. The process or steps for making batik patchwork are: 1) preparing the materials and tools used such as batik patchwork, thread, sewing machine, sewing needle, scissors, pen and paper; 2) Making designs; 3) Selection of batik patchwork; and 4) Making works according to the design. The batik patchwork created in the form of a one-layer mask, a two-layer mask, a tote bag and a sling bag. Based on the results of this study, the factors causing the low creativity of students are influenced by internal factors and external factors.